Biophysical Methods for the Elucidation of the S-Layer Proteins/Metal Interaction - Mobili, Pablo (2013)
Surface-layers (S-layers) are macromolecular paracrystalline arrays of proteins or glycoproteins that can self-assemble into 2-dimensional semi-permeable meshworks to overlay the cell surface of many bacteria and archaea. They usually assemble into lattices with oblique, square or hexagonal symmetry and serve as an interface between the bacterial cell and the environment. Isolated S-layers can recrystallize into two-dimensional regular arrays in suspension or on various surfaces, thus being an appropriate material for several bionanotechnological purposes. Promising applications of S-layers include their use as biotemplates for the capture of metal ions or the synthesis of metal nanoclusters. Considering the use of S-layers as biotemplates for the organization of metal ions or metallic nanoclusters, research on potential of surface layer proteins (SLP) and metals can be understood as an interdisciplinary field, in which different biophysical techniques supply complementary information. In this review, we discuss the SLP as native or engineered “bottom-up” building blocks for metal immobilization structures. We also describe the biophysical techniques used to analyze metal binding properties as well as the information obtained from the investigation of these structures.